Does Home Financing Promote Affordability of Home Ownership in Malaysia? An Empirical Analysis between Islamic and Conventional Banks - Mohd Yusof, Rosylin; Abd Wahab, Norazlina; Hamzah, Hanissah (IIUM Press, 2017)
The aim of this study is to examine the influence of home financing offered by both Islamic and conventional banks and affordability of home ownership (as measured by House Price/GDP per capita) in Malaysia. At the same time, it attempts to assess the effects of employment and interest rate as measured by Overnight Policy Rate (OPR) on home ownership affordability. The study employs the Auto Regressive Distributed Lag Model (ARDL) on yearly data from 2007 to 2014 in order to investigate the link between affordability and selected banking variables such as total home financing by Islamic banks and OPR. Data were extracted from the National Property Information Center (NAPIC) and Bank Negara Malaysia (BNM) Monthly Statistical Bulletin. This study finds that there are cointegrating relationships among all the selected variables at the selected lag length. Home financing of both Islamic and conventional banks were found to be significant in influencing Affordability of Home ownership in Malaysia. Consistent with the fundamentals of Islamic finance, our findings further suggest that OPR (interest rate) is less significant in determining home affordability in the case of Islamic home financing compared to conventional home loan. This study is an empirical attempt to analyze the effect of Islamic home financing as well as conventional loan on affordability. The approach used is technically not new, but it offers better insights into the applicability of Islamic finance in promoting affordability of home ownership. This finding therefore warrants a more in-depth analysis to explore alternative home financing mechanisms such as rental rate pricing to promote home ownership affordability among low to medium income earners in Malaysia